Pengaruh Metode Follow The Line (Ftl) Terhadap Hasil Belajar Siswa Mata Pelajaran Al-Qur’an Hadist Kelas I Madrasah Ibtidaiyah 02 Pondok Modern Muhammadiyah Paciran Lamongan - Nayla Fadiatus Silvia; Himmatul Husniyah (LPPM Sekolah Tinggi Ilmu Tarbiyah Muhammadiyah Bojonegoro, 2024)
This research discusses the influence of the Follow The Line (FTL) learning method on student learning outcomes in Al-Qur'an Hadith subjects Class I Madrasah Ibtidaiyah Muhammadiyah 02 Pondok Modern Paciran for the 2023/2024 academic year. Against the background of students who lack interest in learning to read and write the Al-Qur'an, there are still students who are less accustomed to reading and writing the Al-Qur'an and have different student backgrounds, as well as teachers who still use conventional learning or teachers who dominate the learning process, especially in Al-Qur'an Hadith subjects. To address this problem, researchers are interested in using the Follow The Line (FTL) Learning Method as the main model in the Al-Qur'an Hadith learning process. The formulation of the problem behind the research is